170k views
0 votes
3(x − 1) − 2x = 9

x =

5d + 4(3 − d) = 36
d =

98 − 9y + 10(3 + y) = 213
y =

−58 + 2(h − 29) − h = 41
h =

−67c + 4(17c + 1) = 768
c =

2 Answers

5 votes

Hi Barrett,


1. 3(x − 1) − 2x = 9

3(12 - 1) - 2(12) = 9

3 x 11 - 24 = 9

33 - 24 = 9

x = 12


2. 5d + 4(3 − d) = 36

5d+4(3−d)=36

5d+(4)(3)+(4)(−d)=36

5d+12+−4d=36

(5d+−4d)+(12)=36

d+12=36

d+12=36

d+12−12=36−12

d = 24


3. 98 − 9y + 10(3 + y) = 213

98 - 9(85) + 10(3 + 85) = 213

98 - 765 + 880 = 213

-667 + 880 = 213

y = 85


4. −58 + 2(h − 29) − h = 41

-58 + 2(157 - 29) - 157 = 41

-58 + 256 - 157 = 41

198 - 157 = 41

h = 157


5. −67c + 4(17c + 1) = 768

−67c+4(17c+1)=768

−67c+(4)(17c)+(4)(1)=768

−67c+68c+4=768

(−67c+68c)+(4)=768

c+4=768

c+4=768

c+4−4=768−4

c = 764


Hope This Helps!

User Cory Madden
by
5.4k points
5 votes

1) Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation.

(3 • (x - 1) - 2x) - 9 = 0

Solve x-12 = 0

Add 12 to both sides of the equation

x = 12


2)Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation

(5d + 4 • (3 - d)) - 36 = 0

Solving a Single Variable Equation

d - 24 = 0

Add 24 to both sides of the equation

d = 24


3) ((98 - 9y) + 10 • (y + 3)) - 213 = 0

y - 85 = 0

Solve : y-85 = 0

Add 85 to both sides of the equation :

y = 85


4)(-67c + 4 • (17c + 1)) - 768 = 0

c - 764 = 0

Solve : c-764 = 0

Add 764 to both sides of the equation :

c = 764

User Ramzy Abourafeh
by
6.1k points